2020
DOI: 10.1021/acs.jpclett.0c02355
|View full text |Cite
|
Sign up to set email alerts
|

Defect-Related Broadband Emission in Two-Dimensional Lead Bromide Perovskite Microsheets

Abstract: Low-dimensional hybrid lead halide perovskites (LHPs) with broadband emission (BE) have been developed as promising candidates for single-source white-light-emitting diodes. However, the underlying origin of such BE is poorly understood. Herein, dual-emissive [NH3(CH2)8NH3]­PbBr4 perovskite microsheets (PMSs) with good dispersibility are successfully prepared. Besides the general narrowband emission (NE) originating from free excitons, BE (∼522 nm) is generated under a Br-poor condition, which is not observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 45 publications
3
51
0
Order By: Relevance
“…15 ), However, for the (PEA) 2 SnI 4 and (HA) 2 SnI 4 samples, the TA spectra were characterized by a redshift and a gradual increase in the intensity of the bleaching peak at the band edge with decreasing temperature between 340 and 77 K. Here (PEA) 2 SnI 4 is still applied as the representative material. The redshift of the bleaching peak of component I with a subpicosecond lifetime (277 fs) usually involves different physical processes, such as bandgap renormalization 42 , 43 , optical Stark effect 44 , exciton formation 42 , 45 , and trap states trapping 19 , 46 , 47 . In the recent study of TA kinetics, the component I was attributed to the surface defect trapping exciton process (<1 ps) in 2D (CH 3 (CH 2 ) 8 NH 3 ) 2 PbBr 4 perovskite 47 , the surface trap states trapping exciton process (600 fs) for monolayer MoS 2 materials 46 , and the exciton formation (<1 ps) in monolayer WS 2 materials 42 , 48 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 ), However, for the (PEA) 2 SnI 4 and (HA) 2 SnI 4 samples, the TA spectra were characterized by a redshift and a gradual increase in the intensity of the bleaching peak at the band edge with decreasing temperature between 340 and 77 K. Here (PEA) 2 SnI 4 is still applied as the representative material. The redshift of the bleaching peak of component I with a subpicosecond lifetime (277 fs) usually involves different physical processes, such as bandgap renormalization 42 , 43 , optical Stark effect 44 , exciton formation 42 , 45 , and trap states trapping 19 , 46 , 47 . In the recent study of TA kinetics, the component I was attributed to the surface defect trapping exciton process (<1 ps) in 2D (CH 3 (CH 2 ) 8 NH 3 ) 2 PbBr 4 perovskite 47 , the surface trap states trapping exciton process (600 fs) for monolayer MoS 2 materials 46 , and the exciton formation (<1 ps) in monolayer WS 2 materials 42 , 48 .…”
Section: Resultsmentioning
confidence: 99%
“…The redshift of the bleaching peak of component I with a subpicosecond lifetime (277 fs) usually involves different physical processes, such as bandgap renormalization 42 , 43 , optical Stark effect 44 , exciton formation 42 , 45 , and trap states trapping 19 , 46 , 47 . In the recent study of TA kinetics, the component I was attributed to the surface defect trapping exciton process (<1 ps) in 2D (CH 3 (CH 2 ) 8 NH 3 ) 2 PbBr 4 perovskite 47 , the surface trap states trapping exciton process (600 fs) for monolayer MoS 2 materials 46 , and the exciton formation (<1 ps) in monolayer WS 2 materials 42 , 48 . Several reports have shown that the temperature affects the dielectric shielding effect in the material 49 , 50 , i.e., in the low-temperature phase, the exciton binding energy increases, inducing an increase in the proportion and the formation rate of excitons 50 .…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the spectrum also contains a long tail extending up to 800 nm, which is different from those of the low-dimensional lead–halide hybrids displaying a single sharp excitonic band at absorption onset. 18,53–57 The long tail might be associated with the interband absorption, stemming from multiple defect states. Upon UV light excitation, (C 6 H 8 N) 6 InBr 9 crystals exhibit a warm white-light emission with a color temperature of 5500 K and CIE chromaticity coordinates of (0.33, 0.37), as displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The formed shallow and deep defects in the band gap play different roles in determining the materials’ photophysical processes, and it is known that the deep-level defects might be nonradiative recombination centers, shortening the carrier lifetimes and deteriorating the optical properties, while the shallow-level defects may be PL centers. 37–42 Nevertheless, reports on 0D metal halides with defect-assisted PL are rare, 43–45 and the understanding of the defect properties in this type of material is still in its infancy; thus, there remain many open questions to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36][37][38][39] The double perovskites and low-dimensional perovskites were found to have strong STE emission. [40][41][42][43][44][45][46][47][48] Since the lattice deformation in these structures is easy to occur. In the fully inorganic Cs-Pb-Br systems, the STE emission was mainly discussed in zero-dimensional Cs 4 PbBr 6 , [49][50][51] in which the [PbBr 6 ] À octahedrons are isolated.…”
Section: Introductionmentioning
confidence: 99%